GROUP-BASED HEALTH EDUCATION IN IMPROVING HYPERTENSION CONTROL BEHAVIORS IN COMMUNITIES: A SYSTEMATIC REVIEW - Nara Dikna Aditya; Djazuly Chalidyanto; Rika Ramadhani Makatita (Nursing Sciences Journal, 2026)
Hypertension is a major risk factor for cardiovascular disease and remains one of the leading causes of death worldwide. Despite the availability of effective treatments, poor medication adherence and inadequate self-management continue to hinder optimal blood pressure control. These challenges highlight the need for innovative, community-based strategies to support patients in managing their condition. One such approach is group-based health education, which facilitates shared learning, peer support, and improved patient engagement. This study aimed to evaluate the effectiveness of group-based health education in improving hypertension control behaviors through a systematic review.This review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The PICO framework included adults with hypertension as the population, group-based health education as the intervention, standard care as the comparison, and hypertension control behaviors as the outcomes. These outcomes included reductions in systolic and diastolic blood pressure (SBP and DBP), medication adherence, self-care practices, and overall blood pressure control. Relevant articles were identified through PubMed, Scopus, and Google Scholar using keywords related to hypertension, group education, and community-based interventions. Studies meeting the inclusion criteria were analyzed descriptively. A total of twelve studies, primarily randomized controlled trials from various regions, were included. The findings consistently demonstrated that group-based education significantly improved blood pressure outcomes, adherence, and self-care behaviors. Overall, group-based health education is an effective and sustainable strategy that can be integrated into primary healthcare to enhance long-term hypertension management and patient outcomes.